Analysis of Creative Problem-Solving Learning Models to Improve Thinking Ability Critical to Students - Rezeki Wiranti Wiranti, Fiska (Jurnal Riset Ilmu Pendidikan, 2022)
This research was carried out using the Library Research research methodology, with the aim of knowing the results of the Analysis of Creative Problem-Solving Learning Models to Improve Critical Thinking in Students. This research is based on the occurrence of students who do not understand will improve critical thinking. Based on the results of the analysis of the journal, it states that the Creative Problem-Solving learning model can help solve learning problems for students, with the existence of critical/creative thinking solutions students are easy to respond to problems well and get positive things, and it is appropriate for these students to use the model. to be able to solve existing problems. The results of the study stated that Creative Problem Solving to improve students' critical thinking was very good for solving problems for students and there were positive things seen in the studies above. The model has a very important role in the teaching and learning process. With this learning model, students are expected to be helped in solving the problems that exist in these students. So, from the use of creative problem-solving models it is very feasible to use in the teaching and learning process. This model has also been tested for positive things by previous researchers and obtained results that are feasible to be used in the teaching and learning process in order to solve problems.